2018
DOI: 10.1164/rccm.201706-1288oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bronchodilation, Exercise Training, and Behavior Modification on Symptoms and Physical Activity in Chronic Obstructive Pulmonary Disease

Abstract: Tiotropium/olodaterol, with or without ExT, improved EET in patients with COPD taking part in an SMBM program. Combination bronchodilation, with or without ExT, did not provide additional increases in objective PA compared with SMBM alone but did reduce PA-related dyspnea and difficulty. Clinical trial registered with www.clinicaltrials.gov (NCT02085161).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 40 publications
4
111
1
2
Order By: Relevance
“…A recent study evaluated the benefits of a self‐management behavior modification (SMBM) program in addition to dual bronchodilators and exercise training. The study demonstrated increased physical activity by 10–11 min per day, but exercise and inhaler therapy did not significantly increase physical activity(Troosters et al, 2018). This was surprising given that the study showed evidence of increase exercise endurance testing and resting inspiratory capacity, with an associated reduction in the intensity of dyspnea during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluated the benefits of a self‐management behavior modification (SMBM) program in addition to dual bronchodilators and exercise training. The study demonstrated increased physical activity by 10–11 min per day, but exercise and inhaler therapy did not significantly increase physical activity(Troosters et al, 2018). This was surprising given that the study showed evidence of increase exercise endurance testing and resting inspiratory capacity, with an associated reduction in the intensity of dyspnea during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Tiotropium has been shown to decreases hyperinflation over 24 h and improve continuous work rate endurance on cycle ergometry [122]. Recently, it was shown that dual bronchodilatation improves exercise capacity in patients with COPD participating in a self-management behavior-modification program, irrespective of add-on exercise training [123], emphasizing the importance of lung deflation.…”
Section: Lung Volume Reduction and Pulmonary Rehabilitationmentioning
confidence: 99%
“…Eighty six full text articles were identified and sixty three were excluded by assessing the title and abstract; sixteen out of the twenty three eligible studies were excluded by considering each whole paper and in agreement with reasons reported in Figure 1. Finally, data obtained from 12,690 COPD patients (44.47% treated with T/O 5/5 mg FDC, 43.60% treated with T 5 mg, 11.93% treated with O 5 mg) were extracted from 7 studies including 10 RCTs published between 2015 and 2018 [31][32][33][34][35][36][37].…”
Section: Studies Characteristicsmentioning
confidence: 99%